Economic production of Bacillus subtilis SPB1 biosurfactant using local agro‐industrial wastes and its application in enhancing solubility of diesel. Issue 5 (6th August 2012) - Mnif, Ines; Ellouze‐Chaabouni, Semia; Ghribi, Dhouha
Abstract BACKGROUND: The present work aimed to optimize a new economic medium for lipopeptide biosurfactant production by Bacillus subtilis SPB1 for application in the environmental field as an enhancer of diesel solubility. Statistical experimental designs and response surface methodology were employed to optimize the medium components. RESULTS: A central composite design was applied to increase the production yield and predict the optimal values of the selected factors. An optimal medium, for biosurfactant production of about 4.5 g L−1, was found to be composed of sesame peel flour (33 g L−1) and diluted tuna fish cooking residue (40%) with an inoculum size of 0.22. Increased inoculum size (final OD600) significantly improved the production yield. The emulsifier produced was demonstrated to be an alternative to chemically synthesized surfactants since it shows high solubilization efficiency towards diesel oil in comparison with SDS and Tween 80. CONCLUSION: Optimization studies led to a strong improvement in production yield. The emulsifier produced, owing its high solubilization capacity and its large tolerance to acidic and alkaline pH values and salinity, shows great potential for use in bioremediation processes to enhance the solubility of hydrophobic compounds. © 2012 Society of Chemical Industry